The impact of high frequency oscillatory ventilation on mortality in paediatric acute respiratory distress syndrome - Wong, Judith Ju-Ming; Liu, Siqi; Dang, Hongxing; Anantasit, Nattachai; Phan, Phuc Huu; Phumeetham, Suwannee; Qian, Suyun; Ong, Jacqueline Soo May; Gan, Chin Seng; Chor, Yek Kee; Samransamruajkit, Rujipat; Loh, Tsee Foong; et al. (BMC, 2020)
Background: High-frequency oscillatory ventilation (HFOV) use was associated with greater mortality in adult acute respiratory distress syndrome (ARDS). Nevertheless, HFOV is still frequently used as rescue therapy in paediatric acute respiratory distress syndrome (PARDS). In view of the limited evidence for HFOV in PARDS and evidence demonstrating harm in adult patients with ARDS, we hypothesized that HFOV use compared to other modes of mechanical ventilation is associated with increased mortality in PARDS. Methods: Patients with PARDS from 10 paediatric intensive care units across Asia from 2009 to 2015 were identified. Data on epidemiology and clinical outcomes were collected. Patients on HFOV were compared to patients on other modes of ventilation. The primary outcome was 28-day mortality and secondary outcomes were 28-day ventilator- (VFD) and intensive care unit- (IFD) free days. Genetic matching (GM) method was used to analyse the association between HFOV treatment with the primary outcome. Additionally, we performed a sensitivity analysis, including propensity score (PS) matching, inverse probability of treatment weighting (IPTW) and marginal structural modelling (MSM) to estimate the treatment effect. Results: A total of 328 patients were included. In the first 7 days of PARDS, 122/328 (37.2%) patients were supported with HFOV. There were significant differences in baseline oxygenation index (OI) between the HFOV and non-HFOV groups (18.8 [12.0, 30.2] vs. 7.7 [5.1, 13.1] respectively; p < 0.001). A total of 118 pairs were matched in the GM method which found a significant association between HFOV with 28-day mortality in PARDS [odds ratio 2.3, 95% confidence interval (CI) 1.3, 4.4, p value 0.01]. VFD was indifferent between the HFOV and non-HFOV group [mean difference - 1.3 (95%CI - 3.4, 0.9); p = 0.29] but IFD was significantly lower in the HFOV group [- 2.5 (95%CI - 4.9, - 0.5); p = 0.03]. From the sensitivity analysis, PS matching, IPTW and MSM all showed consistent direction of HFOV treatment effect in PARDS. Conclusion: The use of HFOV was associated with increased 28-day mortality in PARDS. This study suggests caution but does not eliminate equivocality and a randomized controlled trial is justified to examine the true association. © 2020 The Author(s).